THE EFFECT OF AI UTILIZATION AND LEARNING INNOVATION ON STUDENT LEARNING CREATIVITY - Pryditzia Presdiranti; Munirul Abidin (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) utilization and learning innovation on students’ learning creativity. Employing a quantitative associative approach, the research involved 100 university students as the sample. Data were collected using a Likert-scale questionnaire and analyzed through multiple regression after passing validity, reliability, and classical assumption tests. The findings indicate that AI utilization and learning innovation have a significant effect on learning creativity, as reflected by a correlation coefficient of 0.844 and a significance value of 0.000. The results demonstrate that AI contributes to enhancing students’ ability to explore information, generate new ideas, and understand learning materials through adaptive recommendations and feedback. Learning innovation also plays an essential role in creating interactive, flexible, and creativity-stimulating learning environments. The combination of AI utilization and innovative learning strategies provides a richer learning experience and effectively enhances students’ creativity. Learning Innovation, Student Creativity